2007
DOI: 10.1039/b612624c
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to studying aqueous reactions using diffuse reflectance infrared Fourier transform spectrometry: application to the uptake and oxidation of SO2 on OH-processed model sea salt aerosol

Abstract: A new approach to studying aqueous reactions using diffuse reflectance infrared Fourier transform spectrometry: application to the uptake and oxidation of SO2 on OH-processed model sea salt aerosol. Diffuse reflectance infrared Fourier transform spectrometry (DRIFTS) is a powerful technique for analyzing solid powders and for following their reactions in real time. We demonstrate that it can also be applied to studying the uptake and reactions of gases in liquid films. Within the DRIFTS cell, a 10% (w/w) mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 117 publications
(139 reference statements)
0
20
0
Order By: Relevance
“…For example, the reaction of Cl 2 with Br − has a strong surface component, especially at low Cl 2 gas-phase concentrations (Hu et al, 1995). Similarly, Knipping et al (2000) as well as Knipping and Dabdub (2002) suggested a surface reaction between the OH radical and Cl − under atmospheric conditions via formation of a surface complex (Laskin et al, 2003;Shaka' et al, 2007).…”
Section: Well-mixed Surface Reaction Systems [S Rx ]mentioning
confidence: 90%
“…For example, the reaction of Cl 2 with Br − has a strong surface component, especially at low Cl 2 gas-phase concentrations (Hu et al, 1995). Similarly, Knipping et al (2000) as well as Knipping and Dabdub (2002) suggested a surface reaction between the OH radical and Cl − under atmospheric conditions via formation of a surface complex (Laskin et al, 2003;Shaka' et al, 2007).…”
Section: Well-mixed Surface Reaction Systems [S Rx ]mentioning
confidence: 90%
“…Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) has been used successfully for the analysis of solids, and it has applied extensively to study the kinetics and mechanisms of the heterogeneous chemistry on particle surfaces (Vogt and Finlayson-Pitts, 1994;Shaka et al, 2007;Li et al, 2006;Finlayson-Pitts, 2000). The advantage of DRIFTS is that it can be used to measure the reaction products in situ without interrupting the reaction processes (Finlayson-Pitts, 2000).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…European and North American sites may show high levels of TMIs in winter due to increased power generation and emissions, recent results have shown that natural TMIs are likely to be much stronger catalysts of SO 2 oxidation than anthropogenic TMIs (19). At coastal Chinese sites, observations below the modelled line may also point to the importance of oxidation by HOCl and HOBr (61)(62)(63); this pathway has α < 1 (50) and its importance in the marine boundary layer is not well-quantified (61,64,65). Little or no seasonality occurs in the Chinese data.…”
Section: Seasonality In Sulfate Isotopic Compositionmentioning
confidence: 99%